Prevalence of Laboratory Test Results Among Food Handlers and Association with Personal and Environmental Factors at King Chulalongkorn Memorial Hospital, Thai Red Cross Society - Rojdamrongrattana, Nutcha; Assawawitoontip, Surin (Disease Control Journal, 2026)
Foodborne diseases are a major global public health concern. The World Health Organization estimates approximately 600 million cases and 420,000 deaths occur annually. Food handlers play a critical role in preventing such diseases. This study aimed to determine the prevalence of abnormal laboratory findings among food handlers and to examine the associations between personal and environmental factors and those findings at King Chulalongkorn Memorial Hospital, Thai Red Cross Society. A retrospective cross-sectional descriptive study was conducted using retrospectively collected data from 247 food handlers between 2020 and 2024 at King Chulalongkorn Memorial Hospital, Thai Red Cross Society. Variables included sex, age, nationality, duration of employment, type of food establishment, stool culture results, chest X-ray findings, and hepatitis A virus immunity status. Data were analyzed using descriptive statistics and logistic regression analysis, with a statistical significance level set at 0.05. The majority of food handlers were female (75.7%), aged 25–34 years (33.2%), Thai nationals (77.3%), and had been employed for less than 3 years (76.5%). The most common types of establishments were dry food/packaged food shops (41.3%) and retail stores/convenience stores (51.0%). The prevalence of positive stool findings (including both bacterial and parasitic pathogens) was 30.3%. Logistic regression analysis revealed no statistically significant associations between the personal or environmental factors studied and abnormal laboratory findings under this retrospective cross-sectional study design. To identify true risk factors, a more comprehensive risk assessment is warranted. Abnormal laboratory findings should not be used as grounds for permanent exclusion of food handlers; rather, they should serve as information to guide appropriate medical management and follow-up.